The rule of law at the national and international levels : contestations and deference - Kanetake, Machiko; Nollkaemper, André (Studies in international law (Oxford, England) ;, 2016)
This book aims to enhance understanding of the interactions between the international and national rule of law. The book demonstrates that the international rule of law is not merely about ensuring national compliance with international law.